Epigenetic modulation of selected immune response genes and altered functions of T lymphocytes and macrophages collectively contribute to autoimmune diabetes protection - Arathi Jayaraman (Elsevier, 2021)
We have previously demonstrated that weekly treatment of female prediabetic NOD mice with a low dose of the histone deacetylase inhibitor Trichostatin A (TSA) bestowed long-lasting, irreversible protection against autoimmune diabetes. Herein we show that drug treatment diminished the infiltration of the pancreas with CD4+, CD8+ T cells, and Ly-6C+ monocytes. Significantly, TSA administration selectively repressed the expression of a set of genes exaggerated during diabetes and constitutively expressed primarily in the spleen and rarely in the pancreas. These genes encode lymphokines, macrophage-associated determinants, and transcription factors. Although the copy numbers of many histone deacetylases increased during diabetes in the spleen and pancreas, only those upregulated in the spleen were rendered sensitive to repression by TSA treatment. Mitogen-activated T lymphocytes derived from drug-treated donors displayed diminished diabetogenic potential following transfer into immunodeficient NOD.scid mice. In the immunocompromised recipients, diabetes caused by the transfer of activated T lymphocytes from untreated diabetic mice was hampered by the co-transfer of highly purified splenic CD11b+Ly-6C+ macrophages from drug-treated mice. However, the transfer of CD11b+Ly-6C+ macrophages from drug-treated mice failed to block ongoing diabetes in wild-type NOD mice. These data demonstrate that the modified gene expression and functional alteration of T lymphocytes and macrophages collectively contribute to diabetes protection afforded by the histone modifier in female NOD mice.